2018
DOI: 10.1016/j.aott.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate excision time of heterotopic ossification in elbow caused by trauma

Abstract: ObjectiveThe aim of this study was to investigate the optimal timing for the resection of heterotopic ossification (HO) of the elbow.MethodsWe retrospectively reviewed 42 patients who were treated operatively for heterotopic ossification of the elbow from March 2010 to December 2014 at our institution. The patients were divided into early (before 12 months) and late (after 12 months) excision groups. In the early excision group (17 patients), the average time from the initial injury to HO excision was 7.4 (3–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…The exact natural history of heterotopic ossification regarding onset may depend on the location. The time from initial injury to development of ossification has been reported as early as 4 weeks following burn injury and as early as 3 months following elbow injury [27, 28]. One case report suggests that the time from initial injury could be as early as days for development of HO specifically affecting the mesentery [1].…”
Section: Discussionmentioning
confidence: 99%
“…The exact natural history of heterotopic ossification regarding onset may depend on the location. The time from initial injury to development of ossification has been reported as early as 4 weeks following burn injury and as early as 3 months following elbow injury [27, 28]. One case report suggests that the time from initial injury could be as early as days for development of HO specifically affecting the mesentery [1].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, surgeons waited for at least 1 year after initial trauma to intervene surgically, due to a high risk of recurrence of HO [ 37 ]. Recent studies have however, reported good results following an early excision (at < 1 year) with no difference in the HO recurrence rates as compared to a delayed surgery [ 7 , 38 ]. Chen retrospectively reviewed 164 patients with HO, who underwent open arthrolysis, and divided them into two groups, with the HO excision performed at an average 23.0 months after initial injury (range: 9–204 months) and an early excision group, who underwent the excision procedure at average 6.1 months (range: 3–8 months).…”
Section: Discussionmentioning
confidence: 99%
“…40 Early excision (ie, before 12 months after surgery) is recommended, especially for large ossification ( Figure F13 13). 41…”
Section: Imaging Appearance Of Surgical Complicationsmentioning
confidence: 99%
“…Indomethacin and radiotherapy have been used in an effort to prevent heterotopic ossification . Early excision (ie, before 12 months after surgery) is recommended, especially for large ossification (Figure ) …”
Section: Imaging Appearance Of Surgical Complicationsmentioning
confidence: 99%